2016
DOI: 10.22194/jgiass/4.4.766
|View full text |Cite
|
Sign up to set email alerts
|

An Overview: Ginger, a Tremendous Herb

Abstract: Novel nutritional approaches are becoming a major modifiable determinant of chronic diseases. Scientific evidences have supported dietary intervention as an effective tool for healthy life style. In this context, functional foods and nutraceuticals may provide a mean to reduce the increasing burden on health care system by a disease preventive mechanism. Ginger has many biologically active components like polyphenols and flavonoids contain health related properties including anticancer, antiviral and antihyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Ginger (Zingiber officinale) is grown globally for its edible rhizome which has varied utilization in culinary and medicinal applications (Singh, Gangadharappa, & Mruthunjaya, 2017). Shoaib et al (2016) reported that the world's largest producer of ginger is India with a production of more than 30% of the world share followed by China 20.5% while Indonesia, Nepal, and Nigeria produce 12.7%, 11.5%, and 10%, respectively. According to Prasad and Tyagi (2014), the constituents of ginger rhizomes include 50%-70% carbohydrates, 3%-8% lipids, terpenes, and phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Ginger (Zingiber officinale) is grown globally for its edible rhizome which has varied utilization in culinary and medicinal applications (Singh, Gangadharappa, & Mruthunjaya, 2017). Shoaib et al (2016) reported that the world's largest producer of ginger is India with a production of more than 30% of the world share followed by China 20.5% while Indonesia, Nepal, and Nigeria produce 12.7%, 11.5%, and 10%, respectively. According to Prasad and Tyagi (2014), the constituents of ginger rhizomes include 50%-70% carbohydrates, 3%-8% lipids, terpenes, and phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the garlic demonstrated superior effects as compared to ginger alone. Several studies reported lipid lowering effect of ginger (Shoaib et al, 2016); a meta-analysis based study reported the favorable effect of ginger on Triglycerol level and LDL-C, while having no effect on TC and HDL-C. Moreover, the low dose of ginger was found to have greater lowering influence on total cholesterol and Triglycerols (Pourmasoumi et al, 2018).…”
Section: Gingermentioning
confidence: 98%
“…It contains several hundred valuable compounds. It is demonstrated that ginger has a potential to reduce the heart related issues (Shoaib et al, 2016). It inhibits the production of NO, inflammatory cytokines, Cyclo-Oxygenases (COX) and Lipoxygenases (LOX) which oxidizes the arachidonic acid and causes the arterial inflammation (Mojani et al, 2014).…”
Section: Gingermentioning
confidence: 99%
“…Indeed, ginger supplements, ginger oil, ginger powder, ginger tea, and beverages are common nutraceutical products on the market which are heavily consumed. [244] Lemongrass: A mighty resource Cymbopogon citratus (DC.) Stapf, commonly known as lemongrass or citronella, belongs to the Poaceae family and grows in a number of tropical and subtropical regions around the world.…”
Section: Pomegranate: a Fruit With Myriad Virtuesmentioning
confidence: 99%